Cost-effective capacity provisioning in wide area networks with Shoofly - Singh, Rachee; Bjørner, Nikolaj; Shoham, Sharon; Yin, Yawei; Arnold, John; Gaudette, Jamie (ACM SIGCOMM 2021, 2021)
In this work we propose Shoofly, a network design tool that minimizes hardware costs of provisioning long-haul capacity by optically bypassing network hops where conversion of signals from optical to electrical domain is unnecessary and uneconomical. Shoofly leverages optical signal quality and traffic demand telemetry from a large commercial cloud provider to identify optical bypasses in the cloud WAN that reduce the hardware cost of long-haul capacity by 40%. A key challenge is that optical bypasses cause signals to travel longer distances on fiber before re-generation, potentially reducing link capacities and resilience to optical link failures. Despite these challenges, Shoofly provisions bypass-enabled topologies that meet 8X the present-day demands using existing network hardware. Even under aggressive stochastic and deterministic link failure scenarios, these topologies save 32% of the cost of long-haul capacity.